(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Current evidence suggests that MMP and TIMP gene polymorphisms may have a significant impact on the degree of inflammation and structural changes in the myocardium during viral infections, including COVID-19. However, the results of studies remain contradictory due to differences in study groups, methodologies, and evaluation criteria. In addition, most of the studies have focused on general aspects of inflammation in myocarditis, and the exact mechanisms associated with genetic variants in the MMP and TIMP genes are poorly understood.